Evidence for subduction at 3.8 Ga: Geochemistry of arc-like metabasalts from the southern edge of the Isua Supracrustal Belt - Jenner, F E; Bennett, V C; Nutman, A P; Friend, C R L; Norman, M D; Yaxley, G (Research Online, 2009)
We present new major and trace element data for rare examples of preserved pillow basalts from a locality of little studied >3800 Ma rocks at the southwestern edge of the Isua Supracrustal Belt (ISB), West Greenland. The 20 samples have 47.3-59.0 wt.% SiO(2), 4.9-12.2 wt.% MgO, 6.5-11.2 wt.% CaO, 60-340 ppm Ni and 631094 ppm Cr, consistent with pre-metamorphic basaltic compositions. Nb/La((n)) and Ti/Gd((n)) are lower than primitive mantle compositions (0.1-0.6 and 0.3-0.8, respectively), with these ratios interpreted to reflect the composition of their source. Correlations of Nb/La with La/Sm, Ti/Gd and Zr/Sm and between Zr/Nb and Nb/Th are comparable to those of modern subduction related magmas, whereby slab melts enriched the overlying mantle wedge and HFSE were retained by Ti-rich phases. Trends in Ba/La vs. Ba/Nb are comparable to modern day arc related basalts, which reflect a sediment influence and may indicate that, at least early in the evolution of Eoarchean subduction zones, the subducted Eoarchean oceanic crust retained a pelagic sediment cover, with this cover influencing the chemistry of the slab-derived fluid. Three of the ISB pillow lavas show extreme enrichments in LREE (La/Sm((n)) = 1.9-2.6), large depletions in Nb, Ta, Zr and Hf relative to REE that are similar to rare high-K arc basalts from the Clark volcano of the presently active Tongan-Kermadec-New Zealand arc (Gamble, J.A., Christie, R.H.K., Wright, I.C., Wysoczanski, R.J., 1997. Primitive K-rich magmas from Clark volcano, southern Kermadec arc: a paradox in the K-depth relationship. The Canadian Mineralogist, 35, 275-290). The compositions of these highly enriched basalts indicate that the mantle source region of the Isua basalts was occasionally overprinted by small-volume sediment dominated melts rather than hydrous fluids. The compositional affinities of these 3.8 Ga pillow basalts with modern island-arc basalts provide strong evidence for the role of slab fluids and melts in basalt genesis in the Eoarchean, further demonstrating arc-like signatures in the oldest rock sequences. The compositions of Archean mafic rocks including samples from the ISB that are interpreted to have a petrogenesis similar to that of modem island-arc basalts, are compared with Archean 'non-arc' rocks (i.e. plume-related komatiites, komatiitic basalts and associated tholeiitic basalts). The two groups are distinguished by differences in La/Sm, Gd/Yb, Nb/La, Ti/Gd, Ba/La, Ba/Nb and Al(2)O(3)/TiO(2). Thus clear compositional distinctions between different basaltic types, attributed to arc and non-arc origins, are a feature of the rock record for at least the last 3.8 Ga. (C) 2008 Elsevier B.V. All rights reserved